Association of body temperature with in-hospital mortality among paediatric trauma patients: an analysis of a nationwide observational trauma database in Japan. Issue 11 (9th November 2020) - Okada, Asami; Okada, Yohei; Narumiya, Hiromichi; Ishii, Wataru; Kitamura, Tetsuhisa; Osamura, Toshio; Iiduka, Ryoji
Abstract : Objectives: To examine the association between body temperature (BT) on hospital arrival and in-hospital mortality among paediatric trauma patients. Design: A retrospective cohort study. Setting: Japan Trauma Data Bank (JTDB, which is a nationwide, prospective, observational trauma registry with data from 235 hospitals). Participants: Paediatric trauma patients <16 years old who were transferred directly from the scene of injury to the hospital and registered in the JTDB from January 2004 to December 2017 were included. We excluded patients >16 years old and those who developed cardiac arrest before or on hospital arrival. Primary outcome: The association between BT on hospital arrival and in-hospital mortality. We conducted multivariate logistic regression analyses to calculate the adjusted ORs, with their 95% CIs, of the association between BT and in-hospital mortality. Results: A total of 9012 patients were included (median age: 9 years (IQR, 6.0–13.0 years), mortality: 2.5% (mortality number was 226 in total 9012 patients)). In the multivariate logistic regression analysis, the corresponding adjusted ORs of BT <36.0°C and BT ≥37.0°C, relative to a BT of 36°C–36.9°C, for in-hospital mortality were 2.83 (95% CI: 1.85 to 4.33) and 0.93 (95% CI: 0.53 to 1.63), respectively. Conclusions: In paediatric patients with hypothermia (BT <36.0°C) on hospital arrival, a clear association with in-hospital mortality was observed; no such association was observed between higher BT values (≥37.0°C) and outcomes.